Buprenorphine Compared with Methadone in Pregnancy: A Systematic Review and Meta-Analysis. (29th July 2022) - Kinsella, Michael; Halliday, Lucy O. E.; Shaw, Martin; Capel, Yasmin; Nelson, Scott M.; Kearns, Rachel J.
Abstract: Introduction: Illicit opioid use in pregnancy is associated with adverse maternal, neonatal, and childhood outcomes. Opioid substitution is recommended, but whether methadone or buprenorphine is the optimal agent remains unclear. Methods: We searched EMBASE, PubMed, Web of Science, Scopus, Open Gray, CINAHL and the Cochrane Central Registry of Controlled Trials (CENTRAL) from inception to April 2020 for randomized controlled trials (RCTs) and cohort studies comparing methadone and buprenorphine treatment for opioid-using mothers. Included studies assessed maternal and or neonatal outcomes. We used random-effects meta-analyses to estimate summary measures for outcomes and report these separately for RCTs and cohort studies. Results: Of 408 abstracts screened, 20 papers were included (4 RCTs, 16 cohort, 223 and 7028 participants respectively). All RCTs (4/4) had a high risk of bias and median (IQR) Newcastle Ottawa Scale for cohort studies was 7.5 (6–9). In both RCTs and cohort studies, buprenorphine was associated with; greater offspring birth weight (weighted mean difference [WMD] 343 g (95% CI: 40–645 g) in RCT and 184 g (95% CI: 121–247 g) in cohort studies); body length at birth (WMD 2.28 cm (95% CI: 1.06–3.49 cm) in RCTs and 0.65 cm (95% CI: 0.31–0.98 cm) in cohort studies); and reduced risk of prematurity (risk ratio [RR] 0.41 (95% CI: 0.18–0.93) in RCTs and 0.63 [95% CI: 0.53–0.75] in cohort studies) when compared to methadone. All other clinical outcomes were comparable. Conclusions: Compared to methadone, buprenorphine was consistently associated with improved birthweight and gestational age, however given potential biases, results should be interpreted with caution.